Java and Mac OS X - Davis, Gene (Developer reference., 2010)
Provides information on creating Java applications for Mac OS X, covering such topics as Xcode, porting and designing, embedding Cocoa components, understanding JNI, creating terminal applications, and integrating Java controllers.